Grain size effect on magnetic properties of REMnO₃ (RE = Pr, Nd) - Dyakonov, V.; Bażela, W.; Duraj, R.; Dul, M.; Kravchenko, Z.; Zubov, E.; Dyakonov, K.; Baran, S.; Szytuła, A.; Szymczak, H. (Физика низких температур, 2013)
X-ray diffraction and magnetic using dc and ac methods measurements of the polycrystalline and nanosize
REMnO₃ (RE = Pr, Nd) powdered samples have been performed. The nanosize manganites were synthesized
with a sol-gel method at different (800, 850 and 900 °C) temperatures. The average size of synthesized nanoparticles
(from 56 to 89 nm) and polycrystalline powders (above 200 nm) was estimated using the x-ray diffraction
data. All the compounds studied crystallize in the orthorhombic crystal structure (space group Pnma) at room
temperature with smaller values of the lattice parameters in the nanosamples. The temperature-dependent ac
magnetic susceptibilities show a sharp high-temperature peak connected with Mn magnetic moments ordering.
The low-temperature maximum of magnetic susceptibility is proposed to be due to the polarization of the rareearth
sublattice by an effective exchange field of the Mn ordered sublattice. The antiferromagnetic ordering of
Mn sublattice and paramagnetic Curie temperatures as well as the magnetic moment values for the nanosize
samples were found to be smaller than those for polycrystalline sample.